Early Hellenistic marble statue found in Alexandria, Egypt - Limneos Papakosta, Calliope (Technical Annals, 2022)
On 4th of May 2009, in Shallalat Gardens of Alexandria, a marble statue was found, during the excavations held by H.R.I.A.C. (Hellenic Research Institute of Alexandrian Civilization). The statue represents a standing naked man in a form of classical contraposto, with one foot raised, possibly bent to a support. Head and body are in a very good condition, but the part of the legs under the knees is missing. The features of the statue, the attributes and the stylistic analysis are connected with the portraiture of Alexander the Great.